Impact of personality traits on start-up preparation of Hong Kong youths - Zhuang, Jiahao; Xiong, Rui; Sun, Hongyi (Frontiers in Psychology, 2022)
Entrepreneurship is a tool for driving economic and social progress. Especially in Hong Kong, the government has recently taken steps to encourage young people to engage in entrepreneurship. However, Hong Kong youths’ entrepreneurial intentions are still low. The objective of this study is to empirically explore the impacts of personality traits on start-up preparation among Hong Kong youths through the constructs of the theory of planned behavior (TPB). Through a multi-channel survey, we finally collected 230 valid respondents aged 18 to 40. In addition, this study used SmartPLS software to conduct confirmatory factor analysis for the measurement model as well as path analysis for the structural model. This study’s results suggested that creativity, risk-taking propensity, need for achievement, and internal locus of control influence TPB models’ components and indirectly influence start-up preparation through TPB models’ components. Also, attitude and perceived behavioral control influence intention, and intention influences preparation. Furthermore, prior entrepreneurial experience and entrepreneurship education positively influence preparation. In conclusion, this study revealed the mediating effects of TPB components between four personality traits and start-up preparation. Finally, this study had theoretical implications by providing the influence of six personality traits on youths’ entrepreneurial intention and preparation through the TPB model and the human capital theory. This study also had practical implications by providing suggestions for the government and higher education institutions.